DEVELOPMENT COMPOSITE ALUMINIUM/FLY ASH WITH POWDER METALLURGY METHOD USE EGG YOLK AS SPACE HOLDER - Amir Arifin; Gunawan Gunawan; Alim Mardhi; Agung Nurmansyah Putra Wijaya; Endra Sujatmika (Asosiasi Peneliti Sriwijaya, 2021)
Metal matrix composite has been used widely in some applications such as the automotive and aerospace industries. In this work, Aluminum/Fly ash composite material was made with an egg yolk space holder and the manufacturing process was successfully carried out. The process includes the mixing, stirring, drying, and sintering processes that were undertaken including the powder metallurgy method. The metal form has successfully been fabricated however the hardness test results for specimens were not very satisfactory. The Aluminum/Fly ash porous composite materials with egg yolk space holders were was characterized using X-Ray Florence (XRF), X-Ray Diffraction (XRD) test by producing the main peak of Al N and Al2O3. Observation of SEM by showing phenomena such as; cracks, alignment, and porous. Density Testing by producing an average porosity of 28.87%. The observation of Optical Microscopes by showing the shape of the shaft that is not homogeneous.